OrientXplot: a program to analyse and display relative crystal orientations. (1st August 2015) - Angel, Ross; Milani, Sula; Alvaro, Matteo; Nestola, Fabrizio
<x xml:space="preserve">Abstract</x> Orientations of single crystals are usually determined by diffraction experiments. Indexing of a diffraction pattern from one crystal leads to the determination of its `orientation matrix', which defines the orientation of its crystallographic axes relative to a set of reference axes associated with the diffractometer. Crystal orientations can also be described in terms of Euler angles, especially from electron backscattered diffraction measurements. OrientXplot is a Windows program that reads all common types of orientation matrices, as well as orientation data such as Euler angles. The program calculates and displays the relative orientations of pairs of crystals, such as twins or inclusion crystals trapped inside host crystals. OrientXplot can manipulate (under user control) the orientation matrices to allow for ambiguities in indexing that arise from crystal symmetries. Orientation data can be displayed on a stereogram or output in numerical form for plotting in external programs.